Implementing Problem-Based Learning to Support Critical Reading Skills of Junior High School Students at SMPN 15 Bengkulu City - Jaya, Sinarman (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The low reading literacy performance of Indonesian students highlights the need for school programs that help students understand texts more deeply and connect them to real situations.Aims: This community service program is designed to enhance students’ critical reading skills through the use of Problem-Based Learning and to build teacher capacity in applying inquiry-oriented reading activities.Method: The program was conducted over eight sessions and involved twenty-eight students, an English teacher, and a lecturer. Activities included teacher training, classroom mentoring, and the use of problem-based reading materials. Monitoring and evaluation were carried out through classroom observations, teacher reflections, and samples of student work.Results: The implementation of Problem-Based Learning supported by teacher professional development resulted in positive outcomes. Students’ average critical reading scores increased by 23 percent, with positive gains in identifying main ideas, locating key details, comparing information across texts, and understanding academic vocabulary. Student engagement also improved, as learners participated more actively, asked relevant questions, and collaborated more effectively. In addition, the teacher demonstrated increased confidence in guiding inquiry-based reading tasks and facilitating student-centered discussions.Conclusion: The program strengthened students’ reading literacy and supported teacher capacity, demonstrating that PBL is a practical and effective approach for classroom implementation.